Penerapan model pembelajaran kooperatif tipe think pair square pada materi ruang dimensi tiga untuk meningkatkan prestasi belajar matematika siswa kelas X SMA Negeri 1 Baubau - Anwar Anwar; La Eru Ugi (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2017)
The purpose of this classroom action research is to know about the application of cooperative learning model of Think Pair Square type on the material of three-dimensional space (cube) in improving student achievement of class X SMA Negeri 1 Baubau. The subjects of this study involved 38 students of grade X.8 SMA Negeri 1 Baubau. Implementation of this research begins with the test then continued with two cycles of action. Each cycle is done by stages: planning, action implementation, observation/evaluation, and reflection. Data analysis technique used by descriptively qualitative which include data reduction, data presentation and conclusion or verification. Based on the research data, it is found that the learning completeness data on the initial test is 3.23%, the first cycle is 66.67%, and the second cycle is 89.19%. Because of the classical learning completeness criteria set at 75%, it can be concluded that the use of cooperative learning model of Think Pair Square type can improve mathematics learning achievement in students of grade X.8 SMA Negeri 1 Baubau.